Relationships between the second to fourth digit ratio (2D:4D) and game‐related statistics in semi‐professional female basketball players. Issue 1 (12th October 2017) - Dyer, Makailah; Short, Sandra E.; Short, Martin; Manning, John T.; Tomkinson, Grant R.
Abstract: Objective: Digit ratio (2D:4D) is a negative correlate of sports performance, although this relationship may be weak in open‐skill sports such as basketball. The primary aim was to quantify relationships between 2D:4D and game‐related statistics in semi‐professional female basketball players. The secondary aim was to quantify the differences in mean 2D:4Ds between players based on their position in the starting lineup. Methods: Using a cross‐sectional design, 64 female basketball players who competed in the South Australian Premier League were measured in‐season for height, mass, and 2D:4D, with game‐related statistics collected end‐season. Partial correlations (adjusted for age and body mass index) were used to quantify relationships between right and left 2D:4Ds and game‐related statistics. Unpaired t ‐tests were used to quantify differences in mean 2D:4Ds between starting and reserve players. Results: 2D:4D was a substantial negative correlate of blocks, rebounds, and field‐goal percentage; meaning, females with lower 2D:4Ds were generally better defensively as they recorded more blocks and rebounds, and were more efficient scorers, irrespective of their age and body size. Mean 2D:4D differed by position in the starting lineup, as females with lower 2D:4Ds were more likely to be in the starting lineup. Conclusions: This study found evidence that 2D:4D was a correlate of performance in an open‐skill sport. Female players with lower digit ratios tended to perform better in several aspects of basketball, especially defensively, and were more likely to be starters, suggesting they are the best players on the team in their positions. These results probably reflect the organizational benefits of prenatal testosterone.